2004
DOI: 10.1371/journal.pbio.0020217
|View full text |Cite|
|
Sign up to set email alerts
|

Nicotine's Defensive Function in Nature

Abstract: Plants produce metabolites that directly decrease herbivore performance, and as a consequence, herbivores are selected for resistance to these metabolites. To determine whether these metabolites actually function as defenses requires measuring the performance of plants that are altered only in the production of a certain metabolite. To date, the defensive value of most plant resistance traits has not been demonstrated in nature. We transformed native tobacco(Nicotiana attenuata) with a consensus fragment of it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
476
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 425 publications
(486 citation statements)
references
References 37 publications
5
476
1
4
Order By: Relevance
“…AF280402] N. attenuata plants (A-03-108-3), fully characterized in ref. 23, were used as a nicotine-free hostplant to feed M. sexta larvae. Previously characterized N. attenuata transgenic line irCYP (A-09-30-2) was used to silence M. sexta's CYP6B46 (MsCYP6B46 NCBI accession no.…”
Section: Methodsmentioning
confidence: 99%
“…AF280402] N. attenuata plants (A-03-108-3), fully characterized in ref. 23, were used as a nicotine-free hostplant to feed M. sexta larvae. Previously characterized N. attenuata transgenic line irCYP (A-09-30-2) was used to silence M. sexta's CYP6B46 (MsCYP6B46 NCBI accession no.…”
Section: Methodsmentioning
confidence: 99%
“…In N. attenuata, these herbivore-induced defenses include nicotine and TPI (Steppuhn et al, 2004;Zavala et al, 2004b). Because AZ plants have lost their TPI defense mechanism (Wu et al, 2007b), we analyzed the levels of nicotine as well as two phenolic compounds, chlorogenic acid and rutin, which are putative antiherbivore defenses (Isman and Duffey, 1982;Bi et al, 1997) and may constitute part of N. attenuata's direct defense.…”
Section: Ut and Az Produce Different Levels Of Antiherbivory Secondarmentioning
confidence: 99%
“…We found that AZ produces greater amounts of both nicotine and phenolic compounds (chlorogenic acid and rutin) than does UT. Nicotine is a potent chemical defense that has a strong negative effect on M. sexta and on many other herbivores and has been previously shown to be a critical component of JA-mediated direct defense in AZ as well as in UT (Steppuhn et al, 2004). Nicotine biosynthesis is both up-regulated by JA and down-regulated by OS-induced ET (Baldwin, 1998;Voelckel et al, 2001;von Dahl et al, 2007).…”
Section: Natural Variation Of Secondary Metabolitesmentioning
confidence: 99%
“…Alkaloids are a chemically diverse group of lowmolecular weight, nitrogen-containing secondary metabolites with characteristic toxicity and pharmacological activity and may function in the chemical defense of plants against herbivores and pathogens (Facchini, 2001;Steppuhn et al, 2004). Natural hydrophilic products, including alkaloids, are usually stored in the vacuole, which appears to be especially adapted to the bulk storage of chemicals for defensive functions.…”
mentioning
confidence: 99%